A Panel of Biomarkers Is Associated With Increased Risk of the Presence and Progression of Atherosclerosis in Women With Systemic Lupus Erythematosus. Issue 1 (January 2014) - McMahon, Maureen; Skaggs, Brian J.; Grossman, Jennifer M.; Sahakian, Lori; FitzGerald, John; Wong, Weng Kee; Lourenco, Elaine V.; Ragavendra, Nagesh; Charles‐Schoeman, Christina; Gorn, Alan; Karpouzas, George A.; Taylor, Mihaela B.; et al.
<x xml:space="preserve">Abstract</x> Objective An increased frequency of atherosclerosis (ATH) in systemic lupus erythematosus (SLE) is well‐documented but not fully explained by the presence of traditional cardiac risk factors. Several nontraditional biomarkers, including proinflammatory high‐density lipoprotein (piHDL) and leptin, have been individually associated with subclinical ATH in SLE. The aim of this study was to examine whether these and other biomarkers can be combined into a risk profile, the Predictors of Risk for Elevated Flares, Damage Progression, and Increased Cardiovascular Disease in Patients with SLE (PREDICTS), that could be used to better predict future progression of ATH. Methods In total, 210 patients with SLE and 100 age‐matched healthy control subjects (all women) participated in this prospective cohort study. The longitudinal presence of carotid plaque and intima‐media thickness (IMT) were measured at baseline and followup (mean ± SD 29.6 ± 9.7 months). Results At followup, carotid plaque was present in 29% of SLE patients. Factors significantly associated with plaque, determined using Salford Predictive Modeling and multivariate analysis, included age ≥48 years (odds ratio [OR] 4.1, P = 0.002), high piHDL function (OR 9.1, P < 0.001), leptin levels ≥34 ng/dl (OR 7.3, P = 0.001), plasma soluble TWEAK levels ≥373 pg/ml (OR 28.8, P = 0.004), and history of diabetes (OR 61.8, P < 0.001). Homocysteine levels ≥12 μmoles/liter were also a predictor. However, no single variable demonstrated an ideal combination of good negative predictive values (NPVs), positive predictive values (PPVs), sensitivity, and specificity. A high‐risk PREDICTS profile was defined as ≥3 positive biomarkers or ≥1 positive biomarker plus a history of diabetes; for high‐risk SLE patients, the PPV was 64%, NPV was 94%, sensitivity was 89%, and specificity was 79%. In multivariate analysis, SLE patients with the high‐risk profile had 28‐fold increased odds for the longitudinal presence of plaque (P < 0.001) and increased progression of IMT (P < 0.001). Conclusion A high‐risk PREDICTS score confers 28‐fold increased odds of the presence of any current, progressive, or acquired carotid plaque, both in patients with SLE and in control subjects, and is significantly associated with higher rates of IMT progression.